Proceedings of the 12th ACM/IEEE International Symposium on Empirical Software Engineering and Measurement 2018
DOI: 10.1145/3239235.3267427
|View full text |Cite
|
Sign up to set email alerts
|

Measuring human values in software engineering

Abstract: Background: Human values, such as prestige, social justice, and financial success, influence software production decision-making processes. While their subjectivity makes some values difficult to measure, their impact on software motivates our research. Aim: To contribute to the scientific understanding and the empirical investigation of human values in Software Engineering (SE). Approach: Drawing from social psychology, we consider values as mental representations to be investigated on three levels: at a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…The Q-Sort provides quantitative and qualitative data. The quantitative results from our 12-participant study are reported more fully in [37], and so are only briefly summarised here, before moving on to the insight provided by the qualitative data. The qualitative results complement the quantitative data, but also caution against generalisation, demonstrating a more complex picture.…”
Section: Values Q-sort Quantitative Resultsmentioning
confidence: 99%
“…The Q-Sort provides quantitative and qualitative data. The quantitative results from our 12-participant study are reported more fully in [37], and so are only briefly summarised here, before moving on to the insight provided by the qualitative data. The qualitative results complement the quantitative data, but also caution against generalisation, demonstrating a more complex picture.…”
Section: Values Q-sort Quantitative Resultsmentioning
confidence: 99%
“…In the current moment, keeping sight of the underlying ethics and fairness that drive technology initiatives is a primary concern [25]. Efforts are underway to find ways to empirically measure values in software [26]. Value sensitive design methods have arisen to help designers account for and support human values in technology products [27].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, only one software engineering study employed Q-Methodology so far [44], which aimed to understand the viewpoints of human values in software engineering. However, besides medicine, other research fields such as agriculture [19], ecology [2], etc, are taking advantage of this research method.…”
Section: Related Workmentioning
confidence: 99%